Metabolic Syndrome as a Cardiovascular Risk Factor: A Reality or Just a Multiplex of Risk Factors? A Study on Association Between Endothelial Dysfunction And Metabolic Syndrome as a Cardiovascular Risk Factor - Gautam, Mani Prasad; Gautam, Samir; Gangapatnam, Subramanyam; Guruprasad, Sogunuru (Journal of National Heart and Lung Society Nepal, 2023)
Background:Metabolic syndrome is a constellation of various cardiovascular risk factors with a potential to double the risk of coronary artery disease. However, in real world scenario, this is just a combination of multiple CV risk factors and its separate existence is somehow regarded as a myth in endothelial function assessment. Endothelial dysfunction is regarded as a precursor and a surrogate marker of atherosclerosis and coronary artery disease. Therefore a study was designed to evaluate the role of metabolic syndrome as a cardiovascular risk factor by assessing endothelial function in subjects with it. Methods: One hundred subjects with various cardiovascular risk factors were selected and endothelial dysfunction was assessed by measuring flow-mediated dilation of brachial artery. The rates of endothelial dysfunction was compared between subjects with and without metabolic syndrome. Similarly the rates of metabolic syndrome was calculated in subjects with and without endothelial dys-function in this cohorts of cardiovascular risk factors. Results: Out of 100 subjects with cardiovascular risk factors, mean age 46.75 (9.95) years and mean number of risk factors 2.81 (1.17), similarly, there was no significant difference in the rates of metabolic syndrome among subjects with and without endothelial dysfunction (84.85% vs 79.10% respectively; p=0.67). Only age and hypertension were associated with endothelial dysfunction. Conclusion: The association between metabolic syndrome and endothelial dys-function was not significantly different than the association between multiplex of risk factors and endothelial dysfunction. Therefore its putative role as a separate cardiovascular risk factors, rather than just a multiplex still remains under scrutiny if not a myth. Further well-designed study should be conducted to establish the role of metabolic syndrome as a separate cardiovascular risk factor other than just a multiplex.